STUDY ON THE EFFECT OF METALS CONCENTRATION ON BIOCHEMICAL PARAMETERS IN OREOCHROMIS NILOTICUS OF WARWADE RESERVOIR, DUTSE, JIGAWA STATE-NIGERIA - Samira, I. U.; Nafiu, S. A. (FUDMA Journal of Sciences, 2024)
Warwade water Reservoir and Oreochromis niloticus’s tissues (gills and liver) were evaluated by analyzing heavy metals concentrations and their effects on the oxidative stress enzyme from January to August 2022. Both field and laboratory assessments were conducted following established scientific protocols. Monthly sampling occurred between 6:00 – 7:00 am. Four stations denoted as A, B, C, and D, were chosen based on the diversity of anthropogenic activities surrounding the reservoir. The findings showed that heavy metals concentrations in the water ranked as follows: Chromium at 1.96mg/L, followed by Lead (1.74mg/L), Nickel (1.36mg/L), and Cadmium (1.03mg/L). Heavy metals values in fish tissues exhibited a significant decrease (p Cr > Ni > Cd) and liver (Pb > Cr > Cd > Ni). The recorded vlaues exceeded the recommended limits set by WHO (2021). Enzyme activities serving as oxidative stress biomarkers demonstrated a significant reduction (P
Keywords: Antioxidants; Heavy metals; Cichlid fish; toxicity; Warwade Reservoir; Jigawa State